Connecting The Cleaning of Palu Beach With Msme Development: Community Service Efforts For Sustainable Economic Growth - Abdul Jalil; Noval; Irham Pakkawaru; Nuriatullah; Nurfitriani; Indah Handayani (Journal of Community Service: In Economics, Bussiness, and Islamic Finance, 2024)
Beach cleaning is one of the important efforts in maintaining environmental sustainability while also supporting the development of ecotourism. In the city of Palu, community service efforts through beach clean-ups aim not only to improve environmental cleanliness and health but also to encourage local economic growth, particularly through the Micro, Small, and Medium Enterprises (MSMEs) sector. This article examines the relationship between the cleaning of Palu's coastline and the empowerment of local SMEs. In addition, this research also highlights the economic impact generated, both in the form of new job creation in the tourism and MSME sectors, as well as the increased attraction for tourists. Through a community service-based approach, this initiative is expected to strengthen the synergy between environmental conservation and sustainable economic development in Palu. The results show that beach cleanups not only contribute to environmental cleanliness but also provide opportunities for SMEs to grow and play a role in promoting a more sustainable economy.